A Nash equilibrium against gun control - SACCAL, Alessandro (Journal of Mathematical Economics and Finance; Vol 10 No 1 (2024): JMEF, Volume X, Issue 1(18), Summer 2024DO - 10.14505/jmef.v10.1(18).02, 2024)
This work constructs a non-cooperative, static game of gun control between the citizen and a pacifistic society characterised by law enforcement imperfection, by which the retention of firearms and the certitude of punishment against all crimes emerge both as a strict Nash equilibrium, in pure strategies, and as a strict dominant strategy equilibrium. The reason is that ratified by the Second Amendment to the American Constitution, discerning the necessity of a militia to the individual and societal security of a free state, by which the right of the people to keep and bear arms cannot be infringed.